Management of anticoagulation with vitamin K antagonists in a tertiary hospital outpatient clinic - Pivatto Júnior, Fernando; Luis Ferreira da Silva, André; Bárbara Marina Simionato, Bárbara; Fuzinatto, Fernanda; De Conto Oliveira, Jerônimo; Martins Pires, Leonardo; Cristina Petry, Roberta; Selbach Scheffel, Rafael; Carlos Amon, Luís (Clinical and Biomedical Research, 2014)
Introduction: atrial fibrillation (AF) is one of the main risk factors for stroke. Vitamin K antagonists (VKA) reduce this risk, and the effectiveness of this treatment is directly related to time in therapeutic range (TTR). This study aimed to report the TTR in patients with non-valvular AF at an anticoagulation outpatient clinic; and to describe the profile of this population of patients in terms of risk of stroke, as well as the occurrence of adverse events during the follow-up. Methods: Retrospective cohort study involving patients of the anticoagulation outpatient clinic of the Department of Internal Medicine at Hospital de Clínicas de Porto Alegre. We evaluated outpatient visits, hospital admissions, and emergency visits from January to December 2011. TTR was calculated using the Rosendaal method. Results: Sixty-three patients were investigated. Their mean age was 74.3±10.9 years. The CHADS2 score was ≥ 4 in 44.5% of the patients; 63.5% of them had a CHA2DS2-VASc score ≥ 5. The TTR was 64.8%. During follow-up, the incidence of overall bleeding was 31.7%, with major and minor bleeding rates of 4.8% and 34.9%, respectively. There were no other complications related to AF or anticoagulation. Conclusion: The patients achieved a TTR of 64.8% during follow-up, which is deemed appropriate and in agreement with the literature. Patients had high risk for stroke, and the incidence of minor bleeding was higher than the rate found in the literature, whereas the incidence of major bleeding was similar to the one found in previous studies.